Kinetic study of real landfill leachate treated by non-thermal plasma (NTP) and granular sequential batch reactors (GSBR). (October 2021) - Seid-mohammadi, Abdolmotaleb; Asgari, Ghorban; Rafiei, Mohammad; Samadi, Mohammad Thaghi; Nouri, Fatemeh; Pirsaheb, Meghdad; Asadi, Fateme
Abstract: The biological treatment of landfill leachate is a challenging process due to the high concentration of chemical oxygen demand (COD), nitrogen compounds, and other toxic compounds. Furthermore, nitrification inhibition may occur in landfill leachate due to the high concentration of free ammonia and inhibitors, such as poisonous compounds. Accordingly, this study aimed to use non-thermal plasma and aerobic granules to reduce organic loading rate and heavy metals of landfill leachate. We used a plasma reactor with a working volume of 0.5 l, quartz material for the pretreatment process. According to the results, the plasma reactor was most efficient in removing metals as well as d quasi-metals (e.g., arsenic, antimony, selenium, cobalt, iron, strontium, and silver) and least efficient in the removal of nickel, zinc, aluminum, and manganese. Our findings indicated that the COD removal efficiency decreased from 100% to 98%, from 93.5% to 89.18%, and from 92% to 88%, for 20%, 50%, plus 100% leachate, and three hydraulic retention times (6, 4.5, and 2.1 h), respectively. The amount of organic matter removal was a function of concentration and followed the second-order kinetic (R 2  > 0.9) and Stover-Kincannon models (R 2  > 0.97). Thus, it could be concluded that aerobic granules could effectively reduce e the organic load, COD, and heavy metals entering a GSBR reactor. Due to the good efficiency of the plasma reactor and GSBR, so we proposed full- scale studies at the landfill site for heavy metal and organic loading reduction. It also presents a new subject of research and concludes with an outlook on future investigation topics, such as different contaminants in leachate of landfills from different areas. Graphical abstract: Unlabelled Image Highlights: The NTP and GSBR reactors were operated for treatment landfill leachate. One of the factors affecting the efficiency of the GSBR process is organic loading rate. The NTP and GSBR reactors have a high efficiency in removing heavy metals. The kinetics of COD removal was a function of concentration.